PENERAPAN METODE MULTIPLICATIVE DECOMPOSITION DALAM MEMPREDIKSI JUMLAH KASUS DBD DI RSU. HAJI MEDAN - Yulanda Novita Zebua; Sajaratud Dur; Riri Syafitri Lubis (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
DHF case are diseases caused by four types of dengue virus, where each type has its own characteristics and pattern of spread. The purpose of this study is to make predictions on DHF cases in the future. This study uses the Multiplicative Decomposition method, in which this method breaks down time series data into four patterns, namely trend, seasonality, cycles and error. This research was conducted at RSU Haji Medan using DHF case data from January 2017 to December 2021. The results showed that the Multiplicative Decomposition method has an MSE value of 0,0012 and a MAPE value of 0,23%, which means it has a very good accuracy value because less than 10%. The conclusion of the study is that the Multiplicative Decomposition method is a method in the good category in predicting future DHF cases